Heat transfer and second law characteristics of radiator with dissimilar shape nanoparticle-based ternary hybrid nanofluid - Sahoo R.R. (My University, 2025)
In the present study, the heat transfer and second law analysis of radiator with a new coolant of water-based unique shapes nanoparticles, i.e., cylindrical (CNT), blade (Al2O3), and platelet (graphene) ternary hybrid nanofluid, has been investigated. Effect of non-dimensional parameters, thermal performance along with exergetic analysis (entropy generation, second law efficiency, and irreversibility) on Reynolds number and vol. fraction of ternary hybrid nanofluid have been considered. Furthermore, the SEM morphology analysis has been conducted for 1% vol. fraction of ternary hybrid nanofluid. Theoretical comparative analysis revealed that the variation in ternary hybrid concentrations and shape of nanoparticles plays an important role for the enhancement in thermal performance. An increment of 22.34% and 6.63% in heat transfer rate and the second law of efficiency, respectively, has been observed for variation in vol. fraction from 1 to 3% at 10 lpm. The irreversibility of the system increases with the Reynolds number of ternary hybrid nanofluid. However, 12.24% and 19.50% increment in irreversibility and entropy generation, respectively, is observed for change in ternary hybrid concentrations from 1 to 3%. Entropy change for air is greater compared to entropy change in the coolants. Furthermore, non-dimensional parameters have a significant effect on Reynolds number. This inspection divulges on the particle shape and vol. concentrations, which have a critical consequence on the accomplishment of ternary hybrid nanofluids in automotive radiators. © 2020, Akadémiai Kiadó, Budapest, Hungary.